Narrow‐band ultraviolet B therapy attenuates cutaneous T‐cell responses in hapten‐induced, experimental contact dermatitis in beagles. Issue 6 (18th November 2021) - Onishi‐Sakamoto, Saki; Makishi, Kiichi; Takami, Kazumoto; Asahina, Ryota; Maeda, Sadatoshi; Nagata, Masahiko; Moore, Peter F.; Ide, Kaori; Nishifuji, Koji
Abstract : Background: In human medicine, narrow‐band ultraviolet B (NB‐UVB) phototherapy has been used to treat various T‐cell‐mediated skin diseases. However, the effect of NB‐UVB on inflamed canine skin remains uncertain. Objectives: To investigate the effect of NB‐UVB phototherapy on the skin of dogs with hapten‐induced contact dermatitis. Animals: Seven healthy beagles without skin problems. Methods and materials: Dogs were irradiated with varying doses of NB‐UVB to determine the minimal erythema dose (MED). After determining the MEDs of six dogs (excluding one of the seven whose skin did not show a visible reaction), we investigated the effect of NB‐UVB on their inflamed skin by topically applying 2, 4‐dinitrochlorobenzene (DNCB), which causes type 1 helper T cell (Th1)‐ and cytotoxic T‐cell (Tc)1‐induced skin inflammation. We then irradiated the skin with NB‐UVB. We analysed the treated skin samples via histopathological and immunohistochemical methods, and TdT‐mediated dUTP nick‐end labelling (TUNEL) to demonstrate apoptotic cells. We also analysed the cytokine gene transcription via real‐time quantitative reverse transcription PCR. Results: The NB‐UVB MEDs caused mild inflammatory changes yet no severe epidermal exfoliations in the irradiated skin. In DNCB‐treated skin irradiated by the NB‐UVB MEDs, TUNEL‐positive dermal apoptotic cells were increased significantly compared with those of DNCB‐treated, nonirradiated skin. INF‐γ and TNF‐α transcription levels in DNCB‐treated, irradiated skin were significantly lower than those in the DNCB‐treated, nonirradiated skin. Conclusion and clinical relevance: Phototherapy using NB‐UVB MEDs attenuated cutaneous Th1 and Tc1 cytokine responses with minimal skin damage in a canine model of hapten‐induced contact dermatitis. Abstract : Background – In human medicine, narrow‐band ultraviolet B (NB‐UVB) phototherapy has been used to treat various T‐cell‐mediated skin diseases. However, the effect of NB‐UVB on inflamed canine skin remains uncertain. Objectives – To investigate the effect of NB‐UVB phototherapy on the skin of dogs with hapten‐induced contact dermatitis. Conclusion and clinical relevance – Phototherapy using NB‐UVB MEDs attenuated cutaneous Th1 and Tc1 cytokine responses with minimal skin damage in a canine model of hapten‐induced contact dermatitis. Résumé: Contexte: En médecine humaine, la photothérapie ultraviolette B (NB‐UVB) à bande étroite a été utilisée pour traiter diverses maladies de la peau à médiation par les lymphocytes T. Cependant, l'effet de NB‐UVB sur la peau canine enflammée reste incertain. Objectifs: Étudier l'effet de la photothérapie NB‐UVB sur la peau de chiens atteints de dermatite de contact induite par l'haptène. Animaux: Sept beagles en bonne santé sans problèmes de peau. Méthodes et matériel: Les chiens ont été irradiés avec des doses variables de NB‐UVB pour déterminer la dose minimale d'érythème (DEM). Après avoir déterminé les MED de six chiens (à l'exclusion de l'un des sept dont la peau n'a pas montré de réaction visible), nous avons étudié l'effet du NB‐UVB sur leur peau enflammée en appliquant localement du 2, 4‐dinitrochlorobenzène (DNCB), qui provoque un inflammation de type 1 de la peau induite par les lymphocytes T auxiliaires (Th1) et les lymphocytes T cytotoxiques (Tc)1. Nous avons ensuite irradié la peau avec du NB‐UVB. Nous avons analysé les échantillons de peau traités via des méthodes histopathologiques et immunohistochimiques, et le marquage dUTP nick‐end (TUNEL) médié par TdT pour démontrer les cellules apoptotiques. Nous avons également analysé la transcription du gène des cytokines par PCR de transcription inverse quantitative en temps réel. Résultats: Les MED NB‐UVB ont provoqué de légers changements inflammatoires, mais aucune exfoliation épidermique grave de la peau irradiée. Dans la peau traitée au DNCB irradiée par les MED NB‐UVB, les cellules apoptotiques dermiques positives pour TUNEL ont augmenté de manière significative par rapport à celles de la peau non irradiée traitée au DNCB. Les niveaux de transcription d'INF‐γ et de TNF‐α dans la peau irradiée traitée au DNCB étaient significativement inférieurs à ceux de la peau non irradiée traitée au DNCB. Conclusion et pertinence clinique: La photothérapie utilisant des MED NB‐UVB a atténué les réponses des cytokines cutanées Th1 et Tc1 avec des lésions cutanées minimales dans un modèle canin de dermatite de contact induite par l'haptène. Resumen: Introducción: en medicina humana, la fototerapia ultravioleta B de banda estrecha (NB‐UVB) se ha utilizado para tratar diversas enfermedades de la piel mediadas por células T. Sin embargo, el efecto de NB‐UVB sobre la piel canina inflamada sigue siendo incierto. Objetivos: investigar el efecto de la fototerapia NB‐UVB en la piel de perros con dermatitis de contacto inducida por hapteno. Animales: Siete perros Beagle sanos sin problemas en la piel. Métodos y materiales: los perros se irradiaron con dosis variables de NB‐UVB para determinar la dosis mínima de eritema (MED). Después de determinar las MEDs de seis perros (excluyendo uno de los siete cuya piel no mostró una reacción visible), investigamos el efecto de NB‐UVB en su piel inflamada aplicando tópicamente 2, 4‐dinitroclorobenceno (DNCB), que causa inflamación de la piel por tipo 1 linfocito T colaborador (Th1) y linfocito T citotóxico (Tc) 1. Luego irradiamos la piel con NB‐UVB. Analizamos las muestras de piel tratadas a través de métodos histopatológicos e inmunohistoquímicos, y marcaje de extremos rotos (Nick‐end labelling) dUTP mediado por TdT (TUNEL) para demostrar células apoptóticas. También analizamos la transcripción de genes de citoquinas mediante PCR cuantitativa de transcripción inversa en tiempo real. Resultados: las NB‐UVB MEDs causaron cambios inflamatorios leves pero no exfoliaciones epidérmicas graves en la piel irradiada. En la piel tratada con DNCB irradiada por las MEDs de NB‐UVB, las células apoptóticas dérmicas positivas a TUNEL aumentaron significativamente en comparación con las de la piel no irradiada tratada con DNCB. Los niveles de transcripción de INF‐γ y TNF‐α en la piel irradiada tratada con DNCB fueron significativamente más bajos que los de la piel no irradiada tratada con DNCB. Conclusión y relevancia clínica: la fototerapia con NB‐UVB MEDs atenuó las respuestas de las citoquinas cutáneas Th1 y Tc1 con un daño cutáneo mínimo en un modelo canino de dermatitis de contacto inducida por hapteno. Zusammenfassung: Hintergrund: In der Humanmedizin wird die Schmalband Ultraviolet B (NB‐UVB) Phototherapie verwendet, um verschiedene T‐Zell‐mediierte Hauterkrankungen zu behandeln. Die Auswirkung von NB‐UVB auf entzündete Hundehaut bleibt jedoch noch unklar. Ziele: Eine Untersuchung der Auswirkung von NB‐UVB Phototherapie auf die Haut von Hunden mit Hapten‐induzierter Kontaktdermatitis. Tiere: Sieben gesunde Beagles ohne Hautprobleme. Methoden und Materialien: Die Hunde wurden mit unterschiedlichen Dosen an NB‐UVB bestrahlt, um die minimale Erythem Dosis (MED) zu bestimmen. Nach Bestimmung der MEDs bei sechs Hunden (einer der sieben Hunde wurde ausgenommen, da seine Haut keine sichtbare Reaktion zeigte), untersuchten wir die Auswirkung von NB‐UVB auf ihre entzündete Haut durch topische Verabreichung von 2, 3‐Dinitrochlorobenzen (DNCB), welches eine Typ 1 Helfer T Zell (Th1)‐ und zytotoxische T‐Zell (Tc)1‐induzierte Hautentzündung verursacht. Danach wurde die Haut mit NB‐UVB bestrahlt. Wir analysierten die behandelten Hautproben mittels histopathologischer und immunhistochemischer Methoden und TdT‐mediierter dUTP Nick‐Ende Färbung (TUNEL), um apoptotische Zellen zu demonstrieren. Wir analysierten auch die Zytokin Gentranskription mittels Real‐Time Quantitativer Reverser Transkriptions PCR. Ergebnisse: Die NB‐UVB MEDs verursachten in der bestrahlten Haut milde entzündliche Veränderungen, jedoch keine hochgradigen epidermalen Exfoliationen. Bei der DNCB‐behandelten Haut, die mit NB‐UVB MEDS bestrahlt worden war, nahm die Anzahl der TUNEL‐positiven dermalen apoptotischen Zellen im Vergleich zu den mit DNCB‐behandelter, nicht bestrahlter Haut signifikant zu. INF‐γ und TNF‐α Transkriptionswerte bei DNCB‐behandelter, bestrahlter Haut waren signifikant niedriger als jene in der DNCB‐behandelten, nicht bestrahlten Haut. Schlussfolgerungen und klinische Bedeutung: Phototherapie mittels NB‐UVB MEDS verminderte die kutane Th1 und Tc1 Zytokin Antwort bei minimalen Hautveränderungen in einem Hundemodell von Hapten‐induzierter Kontaktdermatitis. 要約: 背景: ヒトでは、ナローバンド紫外線B(NB‐UVB) 光線療法は、様々なT細胞介在性皮膚疾患の治療に用いられている。しかし、炎症を起こした犬の皮膚に対するNB‐UVBの効果はまだ不明である。 目的: 本研究の目的は、ハプテン誘発性接触皮膚炎のイヌの皮膚に対するNB‐UVB光線療法の効果を調査することであった。 被検動物: 皮膚に問題のない健常ビーグル7頭。 材料と方法: 犬に様々な線量のNB‐UVBを照射し、最小紅斑量 (MED) を決定した。6頭の犬 (皮膚が目に見える反応を示さなかった7頭のうち1頭を除く) のMEDを決定した後、1型ヘルパーT細胞 (Th1) および細胞障害性T細胞 (Tc)1誘発性皮膚炎症を引き起こす2, 4‐ジニトロクロロベンゼン (DNCB) を局所的に塗布することで、炎症を起こした皮膚に対するNB‐UVBの効果を調査した。次に、この皮膚にNB‐UVBを照射した。照射した皮膚サンプルは、病理組織学的および免疫組織化学的手法により解析し、TdT‐mediated dUTP nick‐end labelling (TUNEL)によりアポトーシス細胞を検出した。また、リアルタイム定量逆転写PCRでサイトカイン遺伝子の転写を解析した。 結果: NB‐UVB MEDは、照射された皮膚に軽度の炎症性変化を引き起こしたが、重度の表皮剥離はなかった。NB‐UVB MEDを照射したDNCB処理皮膚では, TUNEL陽性の真皮アポトーシス細胞がDNCB処理した非照射皮膚に比べて有意に増加した。DNCB処理した照射皮膚のINF‐γおよびTNF‐α転写レベルは、DNCB処理した非照射皮膚の転写レベルに比べて有意に低かった。 結論と臨床的妥当性: NB‐UVB MEDを用いた光線療法は、ハプテン誘発性接触皮膚炎イヌモデルにおいて、皮膚の損傷を最小限に抑えながら、皮膚のTh1およびTc1サイトカイン反応を弱めた。 摘要: 背景: 在人类医学中, 窄谱中波紫外线(NB‐UVB)光疗已被用于治疗各种T细胞介导的皮肤病。然而, NB‐UVB对犬发炎皮肤的影响仍不确定。 目的: 半抗原诱导出犬接触性皮炎, 研究NB‐UVB光疗对皮肤的影响。 动物: 7只健康比格犬, 无皮肤问题。 方法和材料: 用不同剂量的NB‐UVB照射犬, 测定最小红斑剂量(MED)。在确定了6只犬的MED后 (不包括1只皮肤无可见反应的犬), 我们研究NB‐UVB对发炎皮肤的影响, 通过局部涂抹2, 4‐二硝基氯苯(DNCB), 引起1型辅助性T细胞(Th1)和细胞毒性T细胞(Tc)1诱导的皮肤炎症。然后我们用NB‐UVB照射皮肤。我们通过组织病理学和免疫组织化学方法分析了治疗的皮肤样本, 并通过TdT介导的dUTP缺口末端标记(TUNEL)证明凋亡细胞。我们还通过实时定量逆转录PCR分析了细胞因子基因转录。 结果: NB‐UVB MED在照射皮肤中引起轻度炎症变化, 但无重度表皮剥脱。DNCB处理、经NB‐UVB MEDs照射皮肤, TUNEL阳性真皮凋亡细胞较DNCB处理、未照射皮肤显著增加。DNCB处理、照射皮肤的INF‐γ和TNF‐α转录水平显著低于DNCB处理、未照射皮肤。 结论和临床相关性: 在半抗原诱导的接触性皮炎犬模型中, 使用NB‐UVB MED的光疗减弱了皮肤Th1和Tc1细胞因子反应, 减轻了皮肤损伤。 Resumo: Contexto: Na medicina humana, a fototerapia ultravioleta B de banda curta (NB‐UVB) tem sido usada para tratar várias doenças cutâneas mediadas por células T. No entanto, o efeito de NB‐UVB na pele canina inflamada permanece incerto. Objetivos: Investigar o efeito da fototerapia NB‐UVB na pele de cães com dermatite de contato induzida por hapteno. Animais: Sete beagles saudáveis sem diagnóstico de dermatopatia. Métodos e materiais: Os cães foram irradiados com doses variadas de NB‐UVB para determinar a dose eritema mínima (MED). Depois de determinar as MEDs de seis cães (excluindo um dos sete cuja pele não mostrou uma reação visível), investigamos o efeito de NB‐UVB em sua pele inflamada aplicando topicamente 2, 4‐dinitroclorobenzeno (DNCB), que causa inflamação cutânea mediada por células T‐ helper 1 (Th1) e por células T citotóxicas (Tc) 1. Em seguida, irradiamos a pele com NB‐UVB. Analisamos as amostras de pele tratadas por meio de métodos histopatológicos e imuno‐histoquímicos e marcação com dUTP nick‐end (TUNEL) mediada por TdT para demonstrar células apoptóticas. Também analisamos a transcrição do gene da citocina via PCR de transcrição reversa quantitativa em tempo real. Resultados: As MEDs de NB‐UVB causaram leves alterações inflamatórias, mas não geraram esfoliação epidérmica grave na pele irradiada. Na pele tratada com DNCB irradiada pelas MEDs de NB‐UVB, as células apoptóticas dérmicas positivas para TUNEL aumentaram significativamente em comparação com aquelas da pele não irradiada tratada com DNCB. Os níveis de transcrição de INF‐γ e TNF‐α em pele irradiada tratada com DNCB foram significativamente mais baixos do que na pele não irradiada tratada com DNCB. Conclusão e relevância clínica: A fototerapia com MEDs de NB‐UVB atenuou as respostas cutâneas de citocinas Th1 e Tc1 com injúria cutânea mínima em um modelo canino de dermatite de contato induzida por hapteno.